1995
DOI: 10.1007/bf03349831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two β2-agonist drugs, salbutamol and broxaterol, on the growth hormone response to exercise in adult patients with asthmatic bronchitis

Abstract: The aim of our study was to evaluate the effect of the iv administration of two different beta 2- receptors agonists, salbutamol and broxaterol, on the growth hormone (GH) response to maximal exercise in 11 patients (8 males and 3 females; age range 18-65 yr; mean +/- SE age 56 +/- 13 yr; BMI 26.2 +/- 1.4 kg/m2) with chronic asthmatic bronchitis. All the subjects underwent four cycloergometric exercise tests (incremental workload until maximal predicted heart rate). At baseline, at maximal exercise, at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…We did not find any significant change in basal and endexercise GH secretion between the two treatments but recovery GH appeared markedly blunted by SAL intake. This finding appears in agreement with preceding study describing decrease GH concentration after oral salbutamol intake after both maximal exercise in adult patients with asthmatic bronchitis [4] and submaximal exercise in healthy athletes [3]. It may be suggested that SAL may decrease GH secretion through hypothalamic somatostatin stimulation [4].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find any significant change in basal and endexercise GH secretion between the two treatments but recovery GH appeared markedly blunted by SAL intake. This finding appears in agreement with preceding study describing decrease GH concentration after oral salbutamol intake after both maximal exercise in adult patients with asthmatic bronchitis [4] and submaximal exercise in healthy athletes [3]. It may be suggested that SAL may decrease GH secretion through hypothalamic somatostatin stimulation [4].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, hyperglycaemia and hyperinsulinaemia have often been reported as being associated with the acute use of β-adrenergic agonists [15,20]. Studies on humans also indicate that salbutamol modifies exercise GH secretion both in patients with asthmatic bronchitis and in healthy athletes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The earlier limited data on the effects of acute salbutamol on GH in humans (Giustina et al 1995;Collomp et al 2005;Le Panse et al 2006) have found acute salbutamol administration to decrease exercise GH concentrations, probably via enhanced somatostatin secretion and/or activity. In healthy subjects, acute b 2 stimulation blunts the physiological GH response to both maximal (Collomp et al 2002) and supramaximal exercise (Le Panse et al 2007).…”
Section: Discussionmentioning
confidence: 94%
“…24 Sal (trade name: SALBUMOL 2 mg, tablet, Glaxo-Wellcome Laboratory, Paris, France) was administered 3 h before the test, when maximal pharmacological activity was expected.…”
Section: Salbutamolmentioning
confidence: 99%